Moderate-to-Severe Traumatic Brain Injury - Pasquina, Paul; Kirtley, Robert; Ling, Geoffrey (Seminars in Neurology, 2014)
Managing patients with moderate-to-severe traumatic brain injury (TBI), particularly those with combat-related blast injury, is exceptionally challenging. Optimal care requires the coordinated efforts of numerous providers, contributing to an interdisciplinary team. Given the complexities of TBI and the variety of physiologic, physical, cognitive, behavioral, and emotional manifestations of the injury, a holistic approach to patient care is needed throughout the entire continuum of care. In this article, the authors provide an overview of how interdisciplinary care is provided from the acute to the chronic settings, and illustrate the important role that rehabilitation plays throughout the continuum of care in facilitating maximizing recovery, functional independence, and quality of life. Common conditions associated with TBI are illustrated through a case presentation of an individual with blast-related polytrauma and help to frame a more detailed discussion of subtopics including neurointensive care, posttraumatic seizures, venous thromboembolic disease prevention, spasticity management, vestibular disorders, endocrine dysfunction, and psychological trauma.
Keywords: traumatic brain injury; traumatic brain injury rehabilitation; blast injury; neurointensive care; posttraumatic seizures; deep vein thrombosis spasticity in TBI; heterotopic ossification; vestibular dysfunction; endocrine dysfunction